India Ombudsman: Aspect of Tructural-Institutional and Functional - Derya Ozmen (International Journal of Science and Society, 2020)
Ombudsman is a concept belonging to public administration in general and advocates and protects citizens who are violated of their rights and powers against state institutions. The ombudsman, which finds application areas at different de vlet levels in all continents of the world, is also applied in Asia. The purpose of this article is to provide information on the structural-institutional and functional aspects of the Indian Ombu from Asia. In this context, the place and importance of the ombudsman for Indian democracy and public administration is to be emphasized.